Habitat Potential Model and Efforts to Reduce Risk of Animal Accidents in Arterial Road Between Wangon - Kebasen - Shalihati, Sakinah Fathrunnadi (Forum Geografi, 2014)
The purpose of this study is to determine the potential habitat for each species based on land use and reducing the risk of accidents animals with recommendation traffic signs âWild Animal Crossingâ on the distribution of potential habitat. Qualitative descriptive method was used. The unit of analysis is the villages along the arterial road between Wangon to Kebasen Banyumas. The results show that the potential of the habitat of each species differences , the most widely spread of potential habitat is the narrowest rats and cats and dogs are for the location of this study, and the recommendations of the traffic signs can be placed around the adjacent street or entering potential wildlife habitat with moderate and high classification.